Embracing new techniques and new technologies in cardiac surgery – is it being done responsibly and safely? - Janson, Jacques (SA Heart Journal, 2017)
Cardiac surgeons have been pioneers since the inception of this surgical field. Sixty years ago the development of the heart-lung machine paved the way for cardiac surgery. Since then many new innovations have been introduced, including artificial heart valves, coronary artery bypass grafting, cardiac transplantation, minimally invasive techniques, transcutaneous heart valves and mechanical assist devices. This has required parallel development and advances in medical imaging, such as angiography, echocardiography, CT scanning and MRI providing accurate preoperative diagnosis and optimal planning of surgical procedures.